A Flexural Behavior of Full-Scale RC Beam Strengthened Using Glass Fiber Reinforced Polymer: Experimental Research - Oktalia Wuranti Putri; Angga Fajar Setiawan; Suprapto Siswosukarto; Muhammad Akhsin Muflikhun; Noorsuhada Md Nor; Muslikh (Journal of the Civil Engineering Forum, 2026)
Reinforced Concrete (RC) structures, though strong and economical, may need to be strengthened due to increased load demand for upgraded room functions. Strengthening an RC beam element with Glass Fiber Reinforced Polymer (GFRP) offers flexural strength enhancement, corrosion resistance, and cost efficiency. However, the study that considers the full-scale dimension of a beam strengthened with GFRP is still limited. Therefore, more studies on the flexural strength enhancement of RC beams with GFRP need to be conducted. This research investigated the flexural performance of full-scale RC beams strengthened with externally bonded GFRP. This study involved testing five beam specimens, each with a different number of GFRP layers attached to the outermost tensile zone of the cross-section. Flexural testing was conducted using a four-point bending setup with a loading–unloading scheme to capture the specimens’ elastoplastic behavior, considering recovery during unloading. The analyzed parameters included stiffness, yield strength, debonding strength, ultimate strength, and ductility. Furthermore, the flexural strength was predicted through analytical calculations based on the fiber section method, while the shear strength was estimated following the ACI 318M-14 code. The experimental results showed that GFRP strengthening considerably increased stiffness and first flexural strength of RC beams as a proportion of the number of layers during the pre-debonding state. Despite the debonding occurrence initiating a temporary lapse in the role of GFRP at 0.67% to 0.93% of displacement-span-ratio, it decreased the flexural resistance momentarily. Then, the strengthened beams with two-to-four-layer GFRP still exhibited second ultimate flexural strength enhancement within the range 14.35% to 39.22%. Furthermore, GFRP strengthening generally preserved beam ductility at the second ultimate flexural strength due to the catenary action from debonded GFRP in the plastic hinge zone. Thus, additional GFRP for strengthening RC beams could be effective in the case of a positive bending moment to enhance the stiffness, strength, and ductility